REGULATION LIMITS UNDER CONTROL EFFORT OF SIMO LTI SYSTEMS AND ITS EXTENSION TO DELAY-TIME SYSTEMS - T. BAKHTIAR (Dept. of Mathematics, IPB University, 2006)
In this paper, we investigate regulation properties pertaining to SIMO LTI systems, in which objective function of regulated response is minimized jointly with the control eﬀort. We provide the closed-form solution of the H2 optimal regulation performance for unstable/non-minimum phase continuous-time and discrete-time systems. A direct implication of our main result in- cludes the energy regulation performance of minimum phase time delay systems.